Screening for Atrial Fibrillation in Sub-Saharan Africa: A Health Economic Evaluation to Assess the Feasibility in Nigeria - M. S. Jacobs; A. M. Adeoye; M. O. Owolabi; R. G. Tieleman; M. J. Postma; M. Van Hulst (Ubiquity Press, 2021)
Background: Cardiovascular disease reflects a major burden of non-communicable disease in Sub-Saharan Africa (SSA). Early detection and treatment of atrial fibrillation (AF), as a preventive measure against stroke, is currently not in the scope of the World Health Organization recommendation to reduce cardiovascular disease. Objective: We hypothesized that screening for AF would be an important approach to determine the true AF prevalence in the general population in African countries and to identify asymptomatic AF patients at risk for stroke to optimize prevention. Methods: A decision analytic model was developed to study the health-economic impact of AF screening in Nigeria over a life-time horizon. The patient population explored in the model was a population of newly detected AF cases that would be diagnosed with a one-time systematic screening for AF with a single lead ECG device in community health centres across Nigeria. Conclusions: The health gain per newly detected AF patient (N = 31,687) was 0.41 QALY at a cost of $5,205 per patient with 100% NOAC use, leading to an ICER of $12,587 per QALY gained. The intervention was cost-effective with a 99.9% warfarin use with an ICER of $1,363 per QALY gained. The total cost of a single screening session was $7.3 million for the total screened population in Nigeria or $1.60 per patient screened. Screening for AF to detect AF patients in need for stroke prevention can be a cost-effective intervention in the Sub-Saharan region, depending on type of anticoagulant used and drug costs.